Letter from Hugh S. Taylor to Georg Bredig, March 21, 1940 - Taylor, Hugh S. (Hugh Stott) (1940)
Hugh S. Taylor (1890-1974) expresses his relief that Georg Bredig (1868-1944) was able to immigrate to the United States. Taylor reassures Bredig that there is no pressure to begin his work with Princeton University until his health has sufficiently recovered. Taylor hopes to see Bredig and his son Max (1902-1977) in New York soon.
Keywords: Bredig, Georg, 1868-1944; Taylor, Hugh S. (Hugh Stott), 1890-1974; Emigration and immigration; Princeton University